PENGUATAN KESEHATAN MENTAL SANTRI MELALUI PENDEKATAN PSIKOLOGI ISLAM: IMPLEMENTASI PROGRAM PSIKOEDUKASI DAN KONSELING DI PONDOK PESANTREN CENDEKIA BAZNAS PALEMBANG - Amir Hamzah; Shendy Aulia; Deszarah Aurel Setiawan Putri; Elvina Divaliya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The mental health of students in Islamic boarding schools has become a critical issue due to increasing academic pressure, disciplinary demands, and the social and spiritual adaptation processes they undergo. These conditions can negatively impact psychological well-being if not balanced with appropriate support. This study aims to describe the implementation of a mental health strengthening program based on Islamic Psychology through psychoeducation, peer support, group sharing, mood checks, casual counseling, self-hope letters, the tree of hope, and green action at the Cendekia BAZNAS Islamic Boarding School. The study employed a qualitative descriptive approach using a community service method based on the Recognition-based Community Service Program (KKN). Data collection techniques included observation, informal interviews, documentation, and activity reflections. The results indicated that the program’s implementation had a positive impact on enhancing students’ self-disclosure, interpersonal communication skills, emotional awareness, self-confidence, as well as their social and environmental concern. Relaxed counseling sessions and group sharing activities help students feel more comfortable expressing their feelings and personal issues, while the “letters of hope” and “tree of hope” activities boost students’ motivation and optimism about the future. Thus, an Islamic psychology approach combined with participatory methods has proven effective in holistically supporting the mental well-being of students within the pesantren environment.